DEVELOPMENT OF VALUE-DRIVEN BASIS OF PROSPECTIVE MUSIC TEACHERS PERSONALITY AS A FACTOR OF MULTICULTURAL INTERACTION. - Zadorozhnaya, S.N.; Aisina, S.Т. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
This article considers main aspects of the development of value-driven basis of prospective music teachers’ personality as a factor of multicultural interaction. These aspects are of great importance in the implementation of multiculturalism and are manifested in constant selection and accumulation of spiritual and moral experience, including cultural samples and artifacts of various historical eras. Multiculturalism appears as a consequence of expansion of ideas about world’s musical cultures. Its content in professional and pedagogical preparation of prospective music teachers includes a set of interrelated elements of both social (ethno-cultural, sociocultural, intercultural) and ideological types which are based on the introduction into teaching and learning process of theoretical and practical material, characterized by multicultural orientation.
Keywords: multicultural interaction; personality of prospective music teacher; musical culture; value frameworks